Uji Efektivitas Campuran Herbisida Berbahan Aktif Atrazin dan Topramezon terhadap Beberapa Jenis Gulma - Dad Resiworo Jekti Sembodo; Nana Ratna Wati (JURNAL AGROTROPIKA, 2021)
The purpose of this study was to determine the effectiveness of mixing herbicides with the active ingredients atrazine and topramezone in controlling weeds and to determine the nature of the mixture of the two active ingredients. This research was conducted in a plastic house in Natar District, South Lampung Regency from October 2020 - January 2021. The study was arranged in a Completely Randomized Design (CRD). The treatments consisted of three types of herbicides with six dosage levels of the active ingredients, namely the single herbicide Atrazine 300 g/l (0, 37.5, 75, 150, 300, and 600 g ai ha-1), Topramezon 10 g/l (0. 1.25 , 2.5, 5, 10, and 20 g ai ha-1), and the herbicide mixture of Atrazine 300 g/l + Topramezone 10 g/l (0. 38.75, 77.50, 155, 310, and 620 g ai ha-1) , and repeated 6 times. The target weeds included broadleaf weeds (Ageratum conyzoides and Synedrella nodiflora), grass groups (Digitaria ciliaris, Echinochloa colonum, and Eleusine indica), and the puzzle group (Cyperus iria). The herbicides atrazine and topramezone have different ways of working so that the analytical method used is the Multiplicative Survival Model (MSM) method. The results showed that mixing the herbicide Atrazine 300 g/l + Topramezon 10 g/l had an expected LD50 value of 46.28 g ai ha-1 and a treatment LD50 of 27.22 g ai ha-1 with a co-toxicity value of 1.7 (Co-toxicity > 1) so that it is synergistic.Key words: Atrazin, Topramezon, mixing herbicide, Multiplicative Survival Model, weed, LD50